The Relationship Beetween Family Support and the Quality of Life for the Elderly in Pintubatu Village, Silaen District in 2022 - Mardiati Barus; Samfriati Sinurat; Grace Panjaitan (Sean Institute, 2023)
Family support is the attitude, action, acceptance of the family towards the individual and willing to provide assistance so as to provide a sense of physical and psychological security to the individual in everyday life. Family support has a great effect on the quality of life of the elderly. The elderly who live with their families become a source of support that gives importance to the lives of the elderly. The purpose of this study is to analyze the relationship between Family Support and Quality of Life for the Elderly at Pintubatu Village, Silaen District at 2022. The research method used was a correlation research design with a Cross Sectional approach. Sampling technique with simple random sampling technique with the number of respondents 72 people. The study uses research instruments based on WHOQOL-BREF. The results showe that the majority of family support supported as many as 66 people (91,7%), and the quality of life of the majority was sufficient as many as 54 people (75,0%). The statistical test results of the Spearman Rank test with a p value of 0.000 (p <0.05) indicate that there is a relationship between Family Support and Quality of Life for the Elderly. It is expected that families can maintain and improve personal/social relationships in the elderly so that family support and quality of life in the elderly are in good categories.